The second left-bank castle in Wrocław in the light of the latest archaeological and architectural research - Kmiecik, Piotr; Szwed, Robert (Archaeologia Historica Polona, 2022)
The paper presents the results of archaeological and architectural research on the premises of the former Babiński Hospital at John Paul II Square (plac Jana Pawła II) in Wrocław (Poland), during which the relics of the unfinished second left-bank castle, dating back to the end of the 13th century, were uncovered. Since the 17th century there has been a hypothesis about the existence of a second, nevercompleted left-bank castle, situated on the site of the later building of St. Nicholas’ Arsenal. It was widely discussed in academic papers from the 1940s, as well as by Polish researchers after World War II. This castle was most often associated with the person of Prince Henry IV Probus. The first archaeological investigations which allowed for its preliminary confirmation were carried out in 1979, 1981 and 1992–1994 by a team led by Dr. Jerzy Romanow. Their results, however, did not allow a definitive solution to the problem.